Modelling of controlled drug release from the solid phase through hydrogel membranes - Melnyk, Yuriy; Dzyaman, Iryna; Antoniuk, Viktoria; Skorokhoda, Volodymyr (Видавництво Львівської політехніки, 2013)
The cross-linked copolymers of the 2-hydroxyethylmethacrylate with polyvinylpyrrolidone as granules and membranes were synthesized and their penetration and sorption-desorption properties were investigated. The masstransfer model of hard soluble surface through the hydrogel shell was offered. The developed materials are able to creation as capsule and granule polymer forms of the substances prolonged freeing.
Keywords: hydrogel; 2-hydroxyethyl methacrylate; polyvinylpyrrolidone; sorption; penetration